Iranian L2 Researchers' Perspectives on Research Ethics - Zhila Gharaveisi; Adel Dastgoshadeh (HOW)
This study aims at exploring L2 researchers’ perspectives on research ethics in Iran. A total of ten teacher researchers were selected among a larger group of researchers based on the criteria of academic degree and familiarity with research principles. They were interviewed about different aspects of research ethics. Their responses were audio-recorded and transcribed by the researcher. Finally, the emerging themes were extracted from the responses which showed plagiarism, data management, participant rights, and authorship rights as the most frequent themes discussed by the respondents. Furthermore, the extent of the participants’ self-expressed adherence to ethical considerations in research was differential, ranging from a minimum amount of adherence to an acceptable degree of adherence and commitment to research ethics. In addition, the results showed that not all participants had a clear understanding and definition of the four major themes which emerged from the results.